The Application of Maqasid al-Shariah in the Development of Women's Leadership Model in Malaysia - Atriza Umar; Hamidah Mat (Rabbanica: Journal of Revealed Knowledge)
Women's involvement in the highest leadership positions in Malaysia remains low. Various parties have made multiple efforts to enhance women's empowerment through opportunities in national leadership. This study examines the relevance of the theory of Maqasid al-Shariah as a foundation for developing a leadership model for women in Malaysia. Maqasid al-Shariah's theory, which outlines Islamic law's objectives, offers relevant principles to shape an inclusive leadership model. This qualitative study employs in-depth interviews with experts in Syariah and leadership. The hypothesis assumes that implementing an inclusive leadership model aligned with the principles of Maqasid al-Shariah results in greater social well-being and promotes gender equality in national leadership. The findings of this study provide valuable insights for designers of the women’s leadership model, policymakers, political leaders, and other stakeholders in their efforts to achieve gender equality and social justice in national leadership.